Slimming products: a legal analysis on safety issues in Malaysia / Rohaya Mahmud, Nursyila Roziana Mohd Radzi and Harianty Ghazali - Mahmud, Rohaya; Mohd Radzi, Nursyila Roziana; Ghazali, Harianty (Faculty of Law, 2009)
There are traditional medicines and food products in the market that claim to be effective for losing weight. However, there are cases reported that it had been adulterated with slimming agents that could harm consumers. This study examines the laws and regulations that governed the safety of these products and highlights the weaknesses found in it. The qualitative research methodology is used for this research. The regulatory framework for the slimming products in Malaysia are governed under numerous legislative instruments which provide safeguards over the manufacturing, sale, distribution and advertising of the marketed slimming products. The Poisons Act 1952, the Sale of Drugs Act 1952, the Control of Drugs and Cosmetics Regulation 1984, the Medicines (Advertisement and Sale) Act 1956 and the Food Act 1983 are the statutes that provide the safety standards and requirements for the slimming products marketed in Malaysia. Nevertheless, the penalty imposed for related offences with regards to the slimming products under certain Acts is low to deter the offender, thus an amendment is needed. Although the guidelines and rules are already in place, the cooperation from various sectors especially the regulatory body such as the Drug Control Authority and the enforcement agency is crucial to ensure that the slimming products marketed are safe for the consumer. The industries have to be more responsible in providing the consumer with a safe product. The Pharmacy Enforcement Division of MOH must provide an aggressive consumer education programme to make the consumers aware and consume only safe slimming products.